Isotopic constraints on Davis bank, Vitória-Trindade Ridge: A Revised Petrogenetic Model. (February 2023) - de Oliveira Amaral Quaresma, Gabriella; Costa dos Santos, Anderson; Rocha-Júnior, Eduardo Reis Viana; Bonifácio, Juliana; Queiroz Rego, Caio Assumpção; Mata, João; de Morisson Valeriano, Claudio; Jourdan, Fred; Mattielli, Nadine; Geraldes, Mauro César
Abstract: Davis Bank is the largest and most voluminous volcanic mount in the Vitória-Trindade Ridge (VTR), which comprehends a notable alignment of volcanic features on the South Atlantic Ocean, located at ca . 20°S. The VTR has been interpreted by some authors as the track of the Trindade hotspot impriented on the South American Plate, despite the evident importance of structural control on the ridge. This study presents the first integrated analysis of Sr-Nd-Pb isotopic compositions of Davis Bank to provide new constraints on its magmatic processess. We also present a new whole-rock 40 Ar/ 39 Ar mini-plateau age of 21.42 ± 0.13 Ma (P = 0.49) for one dredged sample from Davis Bank and new geochemical data. The Sr-Nd-Pb isotopic signature of Davis Bank rocks, along with isotopic signatures observed on the Vitória Seamount, are more enriched than the other magmatic manifestations of the VTR. This precludes the derivation of Davis Bank via the exclusive melting of a depleted mantle source, requiring the involvement of one or several enriched components homogenized before eruption. We propose that one of these components is related to the recycled subducted oceanic crust and evolved in an environment with time-integrated low Sm/Nd and slightly high Rb/Sr, U/Pb, and Th/Pb ratios. The enriched component is probably represented by a HIMU-type pyroxenite (hybrid component). Our modeling of the isotopic data indicates that Davis Bank isotopic composition is achieved by a dominant asthenospheric component (DMM) hybridized by the addition of EMI (< 24% in the mixing) and HIMU (up to 20% in the mixture) melts. We further argue that a deep-mantle origin associated with the Trindade Plume hypothesis lacks convincing evidence such as robust geochronological data to attest to the age progression along the VTR. We believe that the Vitória-Trindade Ridge is the surface manifestation of upwelling flow attributed to anomalous fertile shallow sources within a depleted mantle matrix with ubiquitous heterogeneities. Important contributions of detached SCLM fragments and subducted slabs from the Brasiliano Orogeny contaminating the mantle underneath the South Atlantic Ocean are suggested. The presence of such materials in the convective mantle may account for the significant shallow seismic anomalies that have been observed beneath many intraplate volcanic regions in the South Atlantic. Highlights: Ar–Ar dating and Sr-Nd-Pb isotope data of the Davis Bank, Vitória-Trindade Ridge. Identification of a heterogeneous three-component mantle source (DMM, EMI, HIMU). Contribution of recycled Neoproterozoic oceanic lithosphere in VTR mantle source. Brasiliano Orogeny heritage of enriched materials in the mantle underneath VTR. Depleted mantle hybridized by addition of EMI (24%) and HIMU (20%) melts.